Good governance and crime rates in Malaysia - Habibullah, Muzafar Shah; Din, Badariah; Abdul Hamid, Baharom (Emerald Group Publishing, 2016)
Purpose: The purpose of this paper is to relate the quality of governance with crime in Malaysia. The study also identifies the best good governance tool to fight against crime in Malaysia. Design/methodology/approach: The study uses time-series data on crime rates and six measures of governance: voice and accountability, political stability, government effectiveness, regulatory quality, rule of law and control of corruption. In this study the authors employed the popular autoregressive distributed lagged modeling approach to estimate the long-run model of crime and governance. Findings: The authors test the hypothesis that good governance lowers crime rates (total crime, violent and property crimes). The results suggest a negative relationship between crime rates and good governance in Malaysia. This suggests that good governance reduces crime rates in Malaysia. Research limitations/implications: The limitations of this study is the short time-series used in the analysis which is from 1996 to 2009. Practical implications: This study provides evidence that the practice of good governance, for example, lower corruption, good policing and judicial system can mitigate crime in Malaysia. Social implications: The implementation of good governance will protect property right of individuals, business sector and the society as a whole, and this will enhance prosperity of a nation. Originality/value: This study provide the first empirical evidence that linking between crime and good governance in Malaysia.